P5-S6.13 Objective assessment of patient satisfaction with their HIV care. (10th July 2011) - Land, L; Ross, J
Abstract : Background: Patient engagement with HIV services is essential since early diagnosis and care has a direct impact on patient survival and also provides public health benefits associated with reduced infectivity. Positive physician/patient relationships have been linked to higher levels of treatment adherence. Determining and measuring patient priorities in the delivery of HIV services can therefore have a direct impact on perceived satisfaction with services and also improve clinical outcomes. Methods: A systematic review was undertaken to identify existing approaches to identifying patient derived key themes in the delivery of their care. These themes were then examined and expanded using 4 focus groups discussions with HIV services users. Results: A search of 12 bibliographic databases, a hand search of journal bibliographies and a wider internet search yielded 1474 titles from which 150 study abstracts were appraised. 32 articles were retrieved and reviewed using a quality appraisal checklist. A data extraction form was used by two reviewers to extract relevant information for thematic analysis. The review identified key themes of principal importance to patients attending for HIV care—medical staffs' perceived knowledge about HIV, attitude of clinic staff, maintenance of patient dignity, patient autonomy, confidentiality and an appropriate care environment. Three specific survey tools were identified for measuring satisfaction with HIV services but none had wide geographical validity or else failed to reflected current clinical management of HIV disease. The subsequent focus groups supported the findings of the literature review but following the introduction of HAART issues of staff knowledge about HIV were given less prominence. Conclusions: Existing survey tools to measure patient satisfaction with HIV services lack validity or generalisability. The themes identified from this literature review and patient focus groups should be incorporated in the development of future assessment tools.